A DECADE OF STUDIES ABOUT THE HISTORY OF RURAL EDUCATION IN BRAZIL (2012-2022) - Souza-Chaloba, Rosa Fátima [UNESP] (FapUNIFESP (SciELO), 2023)
This text is a bibliographical essay about the production of research on the history of rural education in Brazil in the last decade, reflecting on the studies that have addressed the problems of primary schools and teachers' formation and work in rural areas. The text begins by reconstituting the trajectory of the theme in the field of History of Education, highlighting the contribution of dissertations, theses, and research projects. Then, it discusses some relevant issues to the debate on the theme, especially the conceptual controversies, the historical production of the difference between urban and rural schools, the relations and disagreements between Escola Nova followers and advocates of education ruralization, the transnational circulation of ideas, proposals, and models for rural education, the complex situation of lay teachers and the scope and limits of rural Normal schools and regional Normal courses.
UMA DÉCADA DE PESQUISAS SOBRE A HISTÓRIA DA EDUCAÇÃO RURAL NO BRASIL (2012-2022)
UNE DÉCENNIE DE RECHERCHES SUR L'HISTOIRE DE L'ÉDUCATION RURALE AU BRÉSIL (2012-2022)
Keywords: History of Rural Education; Rural Education; Rural Elementary Schools; Teacher Training for the Rural Environment